Competitive Precinct Projects: The Five Consistent Criticisms of "Global" Mixed-Use Megaprojects. Issue 6 (December 2017) - Harris, Mike
Mixed-use megaprojects on state-owned land have been increasingly occurring around the world over the past few decades. This article reviews the body of literature that has emerged on these projects during this period and investigates a number of projects more deeply by reviewing original planning documents and undertaking interviews with government officials, consultants, and other insiders. Project motives, delivery methods, and built outcomes have been examined in order to contextualize their emergence and proliferation, leading to a typological understanding, defined in this article as competitive precinct projects. A content analysis of 30 reviews covering 42 mixed-use megaprojects in 20 countries reveals remarkable global consistency in thematic criticisms. Framed in this article as the "five consistent criticisms of 'global' mixed-use megaprojects, " they pose a significant barrier to addressing increasingly complex urban challenges as well as to their successful management from inception to delivery. While the consistent criticisms represent patterns that have endured within a globally active urban development type for over three decades, this research shows that rather than being a neoliberal hegemony, there are mixed political and ideological aims and outcomes across projects and sometimes within the same project. A typological understanding allows patterns to be examined and understood, variances and hybridity to be evaluated, and more sophisticated future directions to be mapped out in the pursuit of broader based and city-scale project outcomes.